A study to assess diabetic distress and other factors which affect glycemic control in patients with type 2 diabetes mellitus - Amruthavarshini Nagabhushana; Madhumathi Ramaiah; Mumtaz Ali Khan; Siddesh Nijaguna (APIK Journal of Internal Medicine, 2021)
Objective: The objective of the study was to assess diabetes distress and other factors, which affect glycemic control in patients with type 2 diabetes mellitus (T2DM) and to assess the relation between hemoglobin A1c (HbA1c) and diabetes distress, duration of illness, educational status and treatment modalities, and body mass index (BMI). Methodology: A cross-sectional study conducted at Bangalore Medical College and Research Institute included T2DM patients attending outpatient departments between November 2018 and February 2019, 280 patients were screened for diabetic-related distress using Diabetes Distress Screening Scale (DDS), the patients with diabetes distress were subjected to DDS 17 Questionnaire to determine the type of diabetes distress, and based on score divided into (0–2) little/no distress, (2–2.9) moderate distress, and (3 and more) severe distress. Results: Among 280 patients, 184 patients had diabetic distress and among them, 58.2% had severe distress, 7.5% had moderate distress, 34.3% had little/no distress, 83.1% had emotional burden, 59.2% had physician-related distress, 60.4 had regimen-related distress, and 83% had interpersonal distress. The diabetes distress was significantly associated with age (P = 0.032) and medication adherence (P = 0.00) with educational status. 51.4% had poor glycemic control with HbA1c of >7. The factors significantly associated with poor glycemic control included duration of diabetes with P = 0.008, diabetic distress with P = 0.00, and no significant association with educational status, age, BMI, and treatment modalities. Conclusion: Among type 2 diabetes patients, diabetic distress is a serious problem and needs to be addressed for better glycemic outcome.